Industry 4.0: Job-producer or employment-destroyer? - Enzo Weber (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2016)
This comment discusses the consequences of a potential fourth industrial-digital revolution ('Industry 4.0') from a labour market perspective. In particular, we look at the development through the lens of a comprehensive macroeconomic modelling approach for Germany. Additionally, the significance for public policies is addressed.
Keywords: 330